Building Organizational Citizenship Behavior with Work Motivation: The Role of Job Satisfaction as a Mediating Variable - Bariyah Bariyah; Nanang Ismail Raharjo; Subur Yuswanto; Siti Nur Azizah (Jurnal Economic Resource, 2023)
This study aims to investigate the influence of work motivation in encouraging organizational citizenship behavior in contract employees at PKU Muhammadiyah Gombong Hospital. This study also investigates the role of job satisfaction in mediating the relationship between work motivation and organizational citizenship behavior. This study was carried out using a survey method of 60 contract employees at the PKU Muhammadiyah Gombong Hospital. The data was tested using the SEM-PLS method. The results of the analysis show that work motivation directly influences job satisfaction in a positive direction; Organizational citizenship behavior is significantly influenced by work motivation and job satisfaction in a positive direction. The results of this study also provide empirical evidence that job satisfaction plays a significant role in mediating the relationship between work motivation and organizational citizenship behavior.